A molecular understanding of the interaction of typical aromatic acids with common aerosol nucleation precursors and their atmospheric implications. Issue 62 (6th November 2019) - Wang, Hetong; Zhao, Xianwei; Zuo, Chenpeng; Ma, Xiaohui; Xu, Fei; Sun, Yanhui; Zhang, Qingzhu
Abstract : Aromatic acids, which are generated from numerous anthropogenic emissions and secondary transformations, have been considered to play a crucial role in new particle formation. Abstract : Aromatic acids, which are generated from numerous anthropogenic emissions and secondary transformations, have been considered to play a crucial role in new particle formation. In this study, we performed theoretical calculations at the PW91PW91/6-311++G(3df, 3pd) level to investigate the interaction between typical aromatic acids namely benzoic acid (BA), phenylacetic acid (PAA), phthalic acid (PA), isophthalic acid (mPA), and terephthalic acid (PTA) and common atmospheric nucleation precursors namely sulfuric acid (SA), water (H2 O), ammonia (NH3 ), methylamine (MA), dimethylamine (DMA), and trimethylamine (TMA). The geometric analysis, Gibbs free energy analysis, OH/NH-stretching vibrational frequency calculation, and atoms in molecules (AIM) analysis were conducted to determine the interactions in the complexes. The heterodimers formed a six to eight membered ring through four types of hydrogen bond, and the bond strength could be ranked in descending order: SO–H⋯O > O–H⋯O/N > N–H⋯O. The BA/PAA/mPA/PTA–SA complexes had the lowest Gibbs free energy values. PA was more likely to interact with NH3 or amines rather than SA due to an intra-molecular hydrogen bond. Additionally, the aromatic acids have similar ability to interact with SA and NH3 as monocarboxylic/dicarboxylic acid. The formation potential of the heterodimers from aromatic acids with common nucleation precursors in ambient atmosphere was investigated.